Clinical behavior of chromophobe renal cell carcinoma is less aggressive than that of clear cell renal cell carcinoma, independent of Fuhrman grade or tumor size - Steffens, Sandra; Roos, Frederik C.; Janssen, Martin; Becker, Frank; Steinestel, Julie; Abbas, Mahmoud; Steinestel, Konrad; Wegener, Gerd; Siemer, Stefan; Thueroff, Joachim W.; Hofmann, Rainer; Stoeckle, Michael; et al. (Virchows Archiv, 2014)
Chromophobe renal cell carcinoma (chRCC) is the third most common subtype of RCC, after clear cell (ccRCC) and papillary RCC. Its lower incidence and frequent exclusion from clinical trials might be why chRCC characteristics have not been extensively studied. The aim of our study was to examine tumor characteristics and long-term prognosis of chRCC compared to ccRCC. We collected 4,210 evaluable patients subjected to surgery for chRCC (n = 176) or ccRCC (n = 4,034) at five centers in Germany (University Hospitals of Hannover, Homburg/Saar, Mainz, Ulm, and Marburg) between 1990 and 2010. Patients with chRCC were significantly younger (mean, 60.1 vs. 62.1 years) and tended to be more frequently female (43.8 vs. 36.5 %). Although Fuhrman grade and median tumor diameter were not significantly different, significantly fewer patients with chRCC than with ccRCC presented with high tumor stage or metastasis at diagnosis (18.5 vs. 43.8 %). Moreover, significantly more chRCC patients were treated with partial nephrectomy (41.5 vs. 26.2 %). Accordingly, 5-year cancer-specific survival (CSS) rates were 83.2 % for chRCC against 75.8 % for ccRCC patients (p = 0.014, log rank). However, in multivariate analysis, chromophobe subtype was not confirmed as a significant positive prognostic factor for RCC (HR 0.88, 95 % CI 0.63-1.24; p = 0.48 Cox regression). This is one of the largest studies to date showing that chRCC is associated with a significantly lower risk of locally invasive tumor growth and metastatic disease than ccRCC. We conclude that the clinical behavior of chRCC is less aggressive than that of ccRCC, independent of Fuhrman grade or tumor size.
EVALuna2:6677